Pengetahuan dan Sikap Remaja Terhadap HIV/AIDS - Sawitri, Ni Komang Ari; Aulawi, Khudazi; Nisman, Wenny Artanty (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2006)
Please Refer to The File